Poligami Bagi Aparatur Sipil Negara Berdasarkan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Saragih, Rahmayani (Universitas Muhammadiyah Sumatera Utara, 2018)
Law Number 1 of 1974 concerning Marriage, provisions concerning marriage have been regulated which apply to all Indonesian citizens, including those who are citizens of the status of civil servants. Civil servants must set a good example to their subordinates and set an example as good citizens in the community, also in organizing family life. In Law No. 1 of 1974 stated